Characterization of a GDP-Fucose Transporter and a Fucosyltransferase Involved in the Fucosylation of Glycoproteins in the Diatom Phaeodactylum tricornutum - Zhang, Peiqing; Burel, Carole; Plasson, Carole; Kiefer-Meyer, Marie-Christine; Ovide, Clément; Gügi, Bruno; Wan, Corrine; Teo, Gavin; Mak, Amelia; Song, Zhiwei; Driouich, Azeddine; Lerouge, Patrice; et al. (Frontiers in Plant Science, 2019)
Although Phaeodactylum tricornutum is gaining importance in plant molecular farming for the production of high-value molecules such as monoclonal antibodies, little is currently known about key cell metabolism occurring in this diatom such as protein glycosylation. For example, incorporation of fucose residues in the glycans N-linked to protein in P. tricornutum is questionable. Indeed, such epitope has previously been found on N-glycans of endogenous glycoproteins in P. tricornutum. Meanwhile, the potential immunogenicity of the alpha(1,3)-fucose epitope present on plant-derived biopharmaceuticals is still a matter of debate. In this paper, we have studied molecular actors potentially involved in the fucosylation of the glycoproteins in P. tricornutum. Based on sequence similarities, we have identified a putative P. tricornutum GDP-L-fucose transporter and three fucosyltransferase (FuT) candidates. The putative P. tricornutum GDP-L-fucose transporter coding sequence was expressed in the Chinese Hamster Ovary (CHO)-gmt5 mutant lacking its endogenous GDP-L-fucose transporter activity. We show that the P. tricornutum transporter is able to rescue the fucosylation of proteins in this CHO-gmt5 mutant cell line, thus demonstrating the functional activity of the diatom transporter and its appropriate Golgi localization. In addition, we overexpressed one of the three FuT candidates, namely the FuT54599, in P. tricornutum and investigated its localization within Golgi stacks of the diatom. Our findings show that overexpression of the FuT54599 leads to a significant increase of the alpha(1,3)-fucosylation of the diatom endogenous glycoproteins.